2007
DOI: 10.1890/06-1018
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Different Nitrogen Forms by Coexisting Plant Species and Soil Microbes

Abstract: The growing awareness that plants might use a variety of nitrogen (N) forms, both organic and inorganic, has raised questions about the role of resource partitioning in plant communities. It has been proposed that coexisting plant species might be able to partition a limited N pool, thereby avoiding competition for resources, through the uptake of different chemical forms of N. In this study, we used in situ stable isotope labeling techniques to assess whether coexisting plant species of a temperate grassland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
177
5
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(201 citation statements)
references
References 49 publications
14
177
5
1
Order By: Relevance
“…Error bars are ± 1 SE; there were no statistically significant differences in uptake rates of the two N forms for any species (Table 2) N-form use by Hawaiian plant species (Houlton et al 2007) and Jamaican tree species (Brearley 2013). Plasticity in the use of different N forms may be adaptive if it allows for more effective competition for N resources at the root-level, where availability of different forms can fluctuate on small spatial and temporal scales due to variation in, e.g., mineralization rates, soil moisture, and differential diffusion (Nye 1977;Owen and Jones 2001;Miller and Cramer 2004), as well as competition with neighboring plants and microorganisms (Schimel and Bennett 2004;Harrison et al 2007;Miller et al 2007). Variation among tree species in the capacity to take up differentially available inorganic N forms is thus unlikely to be a dominant mechanism influencing their distributions across soil types in this Bornean rain forest.…”
Section: Discussionmentioning
confidence: 99%
“…Error bars are ± 1 SE; there were no statistically significant differences in uptake rates of the two N forms for any species (Table 2) N-form use by Hawaiian plant species (Houlton et al 2007) and Jamaican tree species (Brearley 2013). Plasticity in the use of different N forms may be adaptive if it allows for more effective competition for N resources at the root-level, where availability of different forms can fluctuate on small spatial and temporal scales due to variation in, e.g., mineralization rates, soil moisture, and differential diffusion (Nye 1977;Owen and Jones 2001;Miller and Cramer 2004), as well as competition with neighboring plants and microorganisms (Schimel and Bennett 2004;Harrison et al 2007;Miller et al 2007). Variation among tree species in the capacity to take up differentially available inorganic N forms is thus unlikely to be a dominant mechanism influencing their distributions across soil types in this Bornean rain forest.…”
Section: Discussionmentioning
confidence: 99%
“…Nature has shown that by routing reactive N through multiple pathways and restricting the flow through nitrification path, N can be cycled more effectively with limited leakage into the environment (Vitousek and Matson, 1984;Cooper, 1986;White, 1991;Northup et al, 1995;Stelzer and Bowman, 1998;Harrison et al, 2007;Ashton et al, 2010;Smolander et al, 2012). As nitrification and denitrification are the two primary biological drivers for the production of NO 3 2 , N 2 O and NO (i.e.…”
Section: The Way Forwardmentioning
confidence: 99%
“…For example, plant d 15 N values reflected a community-wide switch between two mineral N sources along a precipitation gradient in Hawaii (Houlton et al 2006;Schuur and Matson 2001) and among spatially distinct N sources in litter and mineral soils of French Guiana (Schimann et al 2008). Experimental additions of 15 N-enriched tracers have shown that plants prefer mineral over organic forms of N, even in N limited ecosystems (Harrison et al 2007;Ashton et al 2008), and that local adaptations to growth conditions in part determine N uptake rates and preferences for ammonium versus nitrate (Wang and Macko 2011;Andersen and Turner 2013).…”
mentioning
confidence: 99%